National Eye Survey of Trinidad and Tobago (NESTT): prevalence, causes and risk factors for presenting vision impairment in adults over 40 years. Issue 1 (26th March 2019) - Braithwaite, Tasanee; Verlander, Nevile Q; Peto, Tunde; Bartholomew, Debra; Deomansingh, Frank; Bridgemohan, Petra; Saei, Ayoub; Sharma, Subash; Singh, Deo; Ramsewak, Samuel S; Bourne, Rupert R A
Abstract : Aim: To estimate the prevalence, causes and risk factors for presenting distance and near vision impairment (VI) in Trinidad and Tobago. Methods: This is a national, population-based survey using multistage, cluster random sampling in 120 clusters with probability-proportionate-to-size methods. Stage 1 included standardised, community-based measurement of visual acuity. Stage 2 invited all 4263 people aged ≥40 years for comprehensive clinic-based assessment. The Moorfields Eye Hospital Reading Centre graded fundus photographs and optical coherence tomography images independently. Results: The response rates were 84.2% (n=3589) (stage 1) and 65.4% (n=2790) (stage 2), including 97.1% with VI. The mean age was 57.2 (SD 11.9) years, 54.5% were female, 42.6% were of African descent and 39.0% were of South Asian descent. 11.88% (95% CI 10.88 to 12.97, n=468) had distance VI (logarithm of the minimum angle of resolution [logMAR] >0.30), including blindness (logMAR >1.30) in 0.73% (95% CI 0.48 to 0.97, n=31), after adjustment for study design, non-response, age, sex and municipality. The leading causes of blindness included glaucoma (31.7%, 95% CI 18.7 to 44.8), cataract (28.8%, 95% CI 12.6 to 45.1) and diabetic retinopathy (19.1%, 95% CI 4.2 to 34.0). The leading cause of distance VI was uncorrected refractive error (47.4%, 95% CI 43.4 to 51.3). Potentially avoidable VI accounted for 86.1% (95% CI 82.88 to 88.81), an estimated 176 323 cases in the national population aged ≥40 years. 22.3% (95% CI 20.7 to 23.8, n=695) had uncorrected near VI (logMAR >0.30 at 40 cm with distance acuity <0.30). Significant independent associations with distance VI included increasing age, diagnosed diabetes and unemployment. Significant independent associations with near VI included male sex, no health insurance and unemployment. Conclusions: Trinidad and Tobago's burden of avoidable VI exceeds that of other high-income countries. Population and health system priorities are identified to help close the gap.